Impaired Sympathoadrenal Axis Function Contributes to Enhanced Insulin Secretion in Prediabetic Obese Rats - Andreazzi, Ana Eliza (Hindawi Publishing Corporation, 2011)
The involvement of sympathoadrenal axis activity in obesity onset was investigated using the experimental model of treating neonatal rats with monosodium L-glutamate. To access general sympathetic nervous system activity, we recorded the firing rates of sympathetic superior cervical ganglion nerves in animals. Catecholamine content and secretion from isolated adrenal medulla were measured. Intravenous glucose tolerance test was performed, and isolated pancreatic islets were stimulated with glucose and adrenergic agonists. The nerve firing rate of obese rats was decreased compared to the rate for lean rats. Basal catecholamine secretion decreased whereas catecholamine secretion induced by carbachol, elevated extracellular potassium, and caffeine in the isolated adrenal medulla were all increased in obese rats compared to control. Both glucose intolerance and hyperinsulinaemia were observed in obese rats. Adrenaline strongly inhibited glucose-induced insulin secretion in obese animals. These findings suggest that low sympathoadrenal activity contributes to impaired glycaemic control in prediabetic obese rats.